2017
DOI: 10.1002/ange.201702952
|View full text |Cite
|
Sign up to set email alerts
|

Cyanid‐freie und breit anwendbare enantioselektive Syntheseplattform für chirale Nitrile durch einen biokatalytischen Zugang

Abstract: Eine Cyanid-freie Plattformtechnologie zur Synthese von chiralen Nitrilen durch eine biokatalytische,e nantioselektive Dehydratisierung zahlreicher Aldoxime wurde entwickelt. Die Nitrile wurden in vielen Fällen mit Enantiomerenüberschüssen von > 90 %ee( bis zu 99 %ee) erhalten, und eine "privilegierte Substratstruktur" in Hinblick auf das Erzielen einer hohen Enantioselektivitätw urde identifiziert. Des Weiteren wurde ein überraschendes Phänomen bei der Enantiospezifitätb eobachtet, das normalerweise in der Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Cyanide salts are highly toxic, and therefore, cyanide free routes to nitriles are emerging [8] . The research groups of Asano and Gröger reported a number of cyanide‐free syntheses of (aryl‐)aliphatic nitriles by aldoxime dehydratases, including enantioselective reactions [9] . Attempting to utilize biorenewable resources, Gröger and co‐workers started the reaction from aliphatic alcohols available by reducing the biobased fatty acids [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Cyanide salts are highly toxic, and therefore, cyanide free routes to nitriles are emerging [8] . The research groups of Asano and Gröger reported a number of cyanide‐free syntheses of (aryl‐)aliphatic nitriles by aldoxime dehydratases, including enantioselective reactions [9] . Attempting to utilize biorenewable resources, Gröger and co‐workers started the reaction from aliphatic alcohols available by reducing the biobased fatty acids [10] .…”
Section: Introductionmentioning
confidence: 99%